Study on Shear Strength Characteristics of Marine Silt Modified by Steel Slag - Liyan Wang; Bin Zhang; Hongmei Xie; Wenwei Ji; Xiang Huang (Advances in Civil Engineering)
Modern coastal cities continue to expand to the sea, but the marine silt foundation has high water content and poor bearing capacity. Therefore, it is necessary to find economical and rapid ways to reduce the water content of the silt and improve the bearing capacity of the silt foundation. The steel slag is considered to be incorporated into silt to effectively reduce the moisture content of soil and improve the bearing capacity of the foundation due to its hard texture and strong water absorption capacity. In this paper, the shear strength characteristics of marine silt modified by steel slag were studied using an automatic triaxial instrument, as well as the relationship between steel slag incorporation and modified silt density. Experimental results showed that the incorporation of steel slag can effectively improve the shear strength of the silt. Besides, the influences of water content, steel slag incorporation, and confining pressure on the stress-strain curve characteristics and failure deviatoric stress of modified silt were also analyzed. The addition of steel slag increases the failure deviatoric stress of the silt. However, the increase of water content will weaken the effect of steel slag incorporation. The shear strength index of improved silt with different steel slag incorporation was compared with that of traditional soil, verifying the feasibility of its application in engineering construction.